Pressure and rolling torque in high-speed finishing blocks of wire mills with account of mass forces in deformation zones - A. A. Gorbanev; S. M. Zhuchkov; V. V. Filippov; V. A. Tischenko; A. B. Steblov (Литьë и металлургия, 2001)
Tasks of working out of theoretical bases of continuos high-speed rolling of rolled wire are set forth and solved with considerańon of influence of mass forces securing necessary acceleration in deformation zones.